Economic Revitalization of Permaculture Farming Communities in Meratus: Towards Food, Energy, and Locally-Based Economic Independence - Muhammad Azeem Rahman Krisdianto; Siti Halimatussa’diyah Nurissaid; Muhammad Yusfiannor Hidayat; Nofi Utari (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2025)
The Dayak communities in the Meratus Mountains face various structural challenges within their agricultural systems, including declining land productivity, ecosystem degradation, and limited access to markets and current technologies. Traditional shifting cultivation and conventional farming practices are no longer adequate, either ecologically or economically, particularly in the context of environmental change and evolving rural economic dynamics. Therefore, a development approach that integrates ecological, social, and economic efficiency dimensions is urgently needed. This study aims to revitalize the local economy through the implementation of a permaculture-based agroforestry approach. This approach is designed to strengthen ecosystem resilience and enhance farmers’ welfare by utilizing existing biodiversity, optimizing resource efficiency, and fostering mutually beneficial interactions among plant species. The research employs the participatory rural appraisal (PRA) method through training activities, the establishment of demonstration plots, knowledge transfer, and community institutional strengthening to ensure program sustainability and active community participation. The findings indicate that the application of permaculture generates positive economic impacts, increasing farmers’ income by up to IDR 135 million per year, with operational costs of approximately IDR 40 million. The input–output efficiency ratio reaches 2.02, while the income multiplier is recorded at IDR 2.6 million, demonstrating the effectiveness of this approach in creating significant economic value for the community. Socio-ecologically, the program enhances commodity diversification, strengthens food self-sufficiency, and supports land conservation through sustainable cultivation techniques. Additionally, the program contributes to social resilience through increased women’s participation and community-based social regeneration. In conclusion, the permaculture approach has proven to be an effective and superior strategy for sustainable development in the Meratus customary region and is highly suitable for replication in other areas with similar characteristics across Indonesia.